Cold Season Mortality under Natural Conditions and Subsequent Hatching Response of Aedes (Stegomyia) aegypti (Diptera: Culicidae) Eggs in a Subtropical City of Argentina - Gimenez, Javier Orlando (2015)
In temperate and subtropical regions, populations of Aedes (Stegomyia) aegypti (L.) survive unfavorable winter conditions in the egg stage. Knowing their survival rates can be of great interest for the health authorities in charge of control activities. In this study, we analyzed the mortality of Ae. aegypti eggs exposed to the cold season as well as their hatching patterns under laboratory conditions in the city of Resistencia, Chaco, Argentina. The mortality rate was 48.6%. No statistically significant differences were observed in the mortality of eggs exposed at different sites. Hatching response differed significantly among the successive postexposure immersions, with the highest proportion of hatched eggs during the first immersion. These results show that the mortality rate of Ae. aegypti eggs exposed to the cold season in a subtropical city of Argentina was higher than those from temperate climate region. The additional mortality of eggs in our study might be related to fungal development (an unexpected event), which was not observed in research in temperate climate. The hatching pattern observed in this study ensures a rapid increase of the population at the beginning of the favorable breeding season, but it also maintains a batch with delayed hatching eggs, posing a risk for the community.